Reforms in people management: public sector training and development in Malaysia - Shafi, Halim Bin; Fatima, Rebecca (1996)
THE BLUEPRINT Training for Development in West Malaysia 1969, lays the foundation for the establishment of the National Institute of Public Administration (INTAN) in 1972 and the dawning of formal and systematic human resource development in the country. At the same time, the introduction of the New Economic Policy saw greater involvement by the government in the economic development of the country and a phenomenal growth in the size of the civil service with consequent increases in training needs. In INTAN's formative years, training was generic and basic to the functions then required of Malaysian civil servants. This paper outlines the historical perspective of training and development in the Malaysian public sector; the factors contributing towards greater emphasis in training and development; the implications of the paradigm shift on training and development; and issues and challenges in training and development. - Reproduced
Keywords: Administrative reform